Effectiveness of Marketing Mix on the Business Performance of Selected Laundry Shop in Bagong Silang, Caloocan City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Since almost everyone has a hectic schedule due to many activities that need to be fulfilled,there is only limited time to consume, and doing laundry is often left ignored. Businesses likethe selected laundry shop see an opportunity to let people (especially working ones) feel lesstired and stressed doing laundry by offering laundry services such as cleaning, washing, anddrying clothes. The purpose of this study is to determine the effectiveness of the marketingmix in the business performance of selected laundry shops in Bagong Silang, Caloocan City,in terms of age, gender, civil status, number of household members, socioeconomic status,place, price, product, and promotion.The results of the study reveal that the majority of the respondents are female, and ages 21 to30 are the most active age group availing of the services in laundry shops. Most respondentsare single, and in addition, most respondents are in the middle class. The assessment of theeffectiveness of the marketing mix on the business performance of selected laundry shops interms of product, price, place, and promotion is "highly effective." There is no significantrelationship between the effectiveness of the marketing mix and the business performance ofselected laundry shops when the profile is considered. The problems encountered by therespondents are overpricing, availability of laundry detergents, damaged or discoloredclothes, and cleanliness of the clothes.Based on the results of the study, the researchers recommend enhancing the effectiveness ofthe marketing mix on the business performance of selected laundry shops by formulating amarketing strategy that will deal with the 4Ps (place, price, product, and promotion) as well asthe problem(s) encountered by most respondents.
Keywords: Business